One‐Step Soaking Strategy toward Anti‐Swelling Hydrogels with a Stiff "Armor". Issue 9 (22nd January 2023) - Dou, Xueyu; Wang, Hufei; Yang, Fei; Shen, Hong; Wang, Xing; Wu, Decheng
Abstract: Double‐network (DN) hydrogels consisting of noncovalent interacting networks are highly desired due to their well‐controlled compositions and environmental friendliness, but the low water resistance always impairs their mechanical strength. Here, an anti‐swelling hydrogel possessing the core/shell architecture through rational regulation of multiple weak noncovalent interactions is prepared. A composite hydrogel consists of chitosan (CS) and poly( N ‐acryloyl 2‐glycine) (PACG), readily forming the shell‐structured DN hydrogel after soaking in a FeCl3 solution because of in situ formation of chain entanglements, hydrogen bonds, and ionic coordination. The produced DN hydrogels exhibit excellent anti‐swelling behaviors and mechanical durability for over half a year, even in some strict situations. Taking the merits of noncovalent bonds in adjustability and reversibility, the swelling property of these hydrogels can be easily customized through control of the ion species and concentrations. A dynamically reversible transition from super‐swelling to anti‐swelling is realized by breaking up and rebuilding the metal‐coordination complexes. This facile but efficient strategy of turning the noncovalent interactions and consequently the mechanics and anti‐swelling properties is imperative to achieve the rational design of high‐performance hydrogels with specific usage requirements and expand their applicability to a higher stage. Abstract : A soaking strategy is reported to produce a class of tough and anti‐swelling double‐network hydrogels, possessing a dense polymer layer as the protective "armor" through elaborate regulation of noncovalent interactions and thereby the aggregation of polymers. Owing to the dynamic and configurable nature of noncovalent bonds, customized mechanics and swelling are in situ accessed, which endows them adaptive nature applied for different situations.